2011
DOI: 10.1002/jcp.22462
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive overexpression of Id‐1 in mammary glands of transgenic mice results in precocious and increased formation of terminal end buds, enhanced alveologenesis, delayed involution

Abstract: Inhibitor of differentiation-1 (Id-1) has been shown to play an essential role in cell proliferation, invasion, migration, and anti-apoptosis. However, the effect of Id-1 in mammary gland development remains unknown. Here, we generated MMTV-Id-1 transgenic mice to study the role of Id-1 in mammary gland development. In virgin mice, Id-1 overexpression led to precocious development and delayed regression of terminal end buds (TEBs) compared with wild-type mice. The number of BrdU-positive cells and the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Among deleterious shRNAs were those targeting essential genes such as the TATA binding protein (Tbp), which is required for transcription (Table 1 ). Notably, several known regulators of mammary gland morphogenesis and/or epithelial proliferation, such as Ovol2 [ 25 ] and Id1 [ 26 , 27 ], were found to be significantly depleted (Figure 1 D and Table 1 ). Moreover, basally-expressed transcription factors ( Tcf4 and Lef1 ) that are implicated in mammary stem cell renewal through the Wnt pathway were depleted in the functional screen [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among deleterious shRNAs were those targeting essential genes such as the TATA binding protein (Tbp), which is required for transcription (Table 1 ). Notably, several known regulators of mammary gland morphogenesis and/or epithelial proliferation, such as Ovol2 [ 25 ] and Id1 [ 26 , 27 ], were found to be significantly depleted (Figure 1 D and Table 1 ). Moreover, basally-expressed transcription factors ( Tcf4 and Lef1 ) that are implicated in mammary stem cell renewal through the Wnt pathway were depleted in the functional screen [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the greatest increment in the percentage of apoptotic cells was achieved through double knockdown of Id1 and Id3 in N417 cells. It was previously observed that Id proteins could induce apoptosis in some cell types (38-40), but also function as anti-apoptotic molecules in others (41, 42). Our results showed that inhibition of Id1 and Id3 promoted apoptosis of N417 cells in response to cisplatin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…After the tumors were dissected, IHC analysis was performed using consecutive sections of tumors from 3 independent xenografted mice as described previously (13,48). The results were scored by multiplying the percentage of positive cells by the staining intensity as described in the IHC staining section.…”
Section: Methodsmentioning
confidence: 99%